(untitled) (E Global Congress, 2025)
This article discusses the recent global climate change, energy resource depletion, and environmental challenges that have led countries to focus on sustainable development. One of the key strategies to achieve this is the use of renewable energy sources and the introduction of energy-saving technologies. These solutions are not only environmentally beneficial, but also economically beneficial in the long term. Uzbekistan has taken active steps in this direction by adopting national strategies to support green energy and sustainability. The financial sector plays a crucial role in this process by offering green financing mechanisms. Among them, the “Green Energy Credit Passport” introduced by Davr Bank PJSCB stands out as an important financial instrument aimed at popularizing renewable energy sources among legal entities. This dissertation studies the objectives, conditions, and impact of this credit product, analyzing its contribution to sustainable economic and environmental development.